Mapping Engineering and Development Research Excellence in the UK: An Analysis of REF2014 Impact Case Studies. (21st October 2016) - Robbins, Peter T.; Wield, David; Wilson, Gordon
Abstract: For the first time, the UK research evaluation system, known as the Research Excellence Framework, considered 'measures' of impact in the 2014 review. Here, we focus on impact case studies that had an engineering and international development orientation. We found that writers of impact case studies commonly chose to employ an ecological modernization (economic, environmental, and social value) discourse to shape value claims. We also found that the type of engineering and international development research that appears in impact case studies tends to be high tech, best‐with‐best, and exclusive, rather than low tech, humanitarian, and inclusive.